School to work transition: employment and expectations of former madrasa students in Cox’s Bazar, Bangladesh - Ahmed, MS; Arman, MR; Hossain, M; Rahman, KW; Rahman, NT (Elsevier, 2024)
We document the dynamics of the school-to-work transition of former madrasa students in Cox’s Bazar, Bangladesh – the host community of the Rohingya refugees. We conduct a phone survey using a respondent-driven sampling (RDS) technique to understand the labour market opportunities and aspirations of former madrasa students in Cox’s Bazar who are 15–40 years old. We find that most of the respondents are in the labour market, with male respondents driving this trend. There is a strong willingness to participate in training and expectations that receiving training will double income. We report that there is a mismatch between the actual and desired sector of employment– most of the employed respondents want to engage in different income-generating activities than their current ones. We also find gender differences in the types of training desired and expected income.